Evaluasi Tekno-Ekonomi dan Lingkungan Co-Firing Biomassa pada PLTU CFB di Nusa Tenggara Timur - Andi Wulan; Sidqi Muhammad Ahsin (Politeknik Negeri Malang, 2026)
This study evaluates the technical, economic, and environmental performance of biomass co-firing implementation at the Bolok Coal-Fired Power Plant (CFB type) in East Nusa Tenggara. The study aims to assess the impact of biomass substitution on plant performance and to analyze uncertainty associated with key operational parameters. A deterministic analysis was conducted using what-if scenarios, while uncertainty was evaluated through Monte Carlo simulation with 10,000 iterations. Technical performance was assessed using Specific Coal Consumption (SCC), economic performance was evaluated based on fuel cost, and environmental performance was measured through CO₂ emission reduction. The results indicate that SCC ranges from 0.85 to 1.08 kg/kWh with an average value of 0.96 kg/kWh. Fuel cost ranges from IDR 991,314.93 to IDR 1,352,002.53 per MWh, while CO₂ emission reduction ranges from 2,711.85 to 5,796.49 tonCO₂. The findings show that increasing the co-firing ratio contributes to significant emission reduction while maintaining fuel cost within an acceptable range, although specific fuel consumption tends to increase due to the lower calorific value of biomass. Monte Carlo simulation reveals that economic variables, particularly biomass price, have the greatest influence on uncertainty compared with technical and environmental variables. The main contribution of this study lies in the integration of technical, economic, environmental, and probabilistic analyses using actual operational data from a CFB power plant, providing a more comprehensive basis for evaluating biomass co-firing implementation under uncertain operating conditions.